PENGARUH KUALITAS PRODUK, BRAND AMBASSADOR, DAN INOVASI PRODUK TERHADAP MINAT BELI ULANG PADA INDOMIE DI MAGELANG - Linanti Sally Andini; Atmaja, Hanung Eka; Ratnawati, Shinta (PT Naureen Digital Education, 2025)
This study is based on the phenomenon of inconsistent findings in previous research regarding repeat purchase intention of Indomie in Magelang. The purpose of this research is to determine the influence of product quality, brand ambassador, and product innovation on repeat purchase intention based on the Theory of Planned Behavior (TPB). This research uses a quantitative approach with a survey method through the distribution of questionnaires to Indomie consumers in Magelang. The sampling technique used is non-probability sampling with criteria of respondents aged at least 17 years and having consumed Indomie. The results of the study show that product quality and brand ambassador have a positive influence on repeat purchase intention, while product innovation does not have a significant effect on repeat purchase intention. Keywords: Repurchase Intention, Product Quality, Brand Ambassador, Product Innovation